Development of Mathematics Learning Media Training Based On Realistic Mathematics For Teacher Of Integrated Islamic Elementary School In District Sleman And Bantul - Ali Mahmudi; Jailani Jailani; Wahyu Setyaningrum; Tuharto Tuharto; Fitriana Yuli Saptaningtyas; Muhammad Fauzan (Yogyakarta State University, 2018)
This community service is aimed at introducing realistic mathematics learning approach in elementary school and training of teachers to develop creative and meaningful mathematics learning media with Islamic context. This activity takes the form of training to deepen the learning materials and develop the Islamic context in the learning of mathematics. The technical steps in this activity are explanation and discussion about the importance of paying attention to the child's cognitive development stage in implementing the learning to be meaningful for the students. The next stage is an explanation and discussion of realistic mathematics learning approaches and appropriate learning media that use meaningful daily context for students. Furthermore, a workshop was held to develop realistic learning media with an Islamic context. Based on the observation and discussion with the participants it can be concluded that the participants enthusiastically attend the training. Participants also identified and acquired new ideas to develop realistic elementary-based mathematics learning media with an Islamic context. Such media is expected to motivate students to learn mathematics because it uses approach and learning media meaningful for students.